23.
[tex]a)\\2*(-2)^2-6*(-\frac12)=2*4+3=8+3=11\\\\b) \\\frac{(-\frac12)*\frac23}{-\frac34}=-\frac43*((-\frac12)*\frac23)=-\frac43*(-\frac26)=-\frac{2}3*(-\frac23)=\frac49\\\\c)\\\frac{-2}2+\frac{4,2}3-\frac{-3,6}6=-1+1.4+0.6=1[/tex]
[tex]d)\\(4*(-\frac12)-3)(3*(-\frac12)+2)-(-\frac12)((-\frac12)-1)=\\(-2-3)(-\frac32+\frac42)-(\frac14+\frac24)=\\-5*\frac12-\frac34=\\-\frac{10}4-\frac34=-\frac{13}4=-3\frac14[/tex]
[tex]e) \\\frac{-\frac15}{0.1}-\frac{-\frac15+0.1}{3*(-\frac15)}=-\frac15*\frac{10}1-\frac{-\frac2{10}*\frac1{10}}{-\frac35}=-2-(-\frac53)*(-\frac1{10})=-2-\frac{5}{30}=-2\frac{5}{30}=-2\frac16[/tex]
[tex]f) \\4*\frac14*(-3)^2*(-0.5)^3=1*9*(-0.125)=9*(-0.125)=-1.125[/tex]
24.
[tex]10-2^2-2=10-4-2=6-2=4\\Odp. D[/tex]
25.
[tex]\\2*(-3\sqrt3)^2-\sqrt2*(-\sqrt2)^3=2*27-\sqrt2*(-2\sqrt2)=54+4=58\\Odp. B[/tex]